Preliminary study on the use of microwave permittivity in the determination of asphalt binder penetration and viscosity - Muniandy, Ratnasaamy; A. Aziz, Md. Manniruzaman; Hassim, Salihudin (2012)
Asphalt binder analysis and grading have gone through many stages of facelift starting from the conventional tests such as penetration and viscosity to the recent use of superpave binder test and grading system. Although these approaches have laid the foundation for the testing and grading of asphalt binders, it is observed that the time frame involved and the cost of testing and equipment are rather costly. As such, a new approach using microwave technique was carried out to see if there can be any correlation established between the penetration-viscosity values and the measured microwave permittivity. This paper looks into the use of microwave frequencies from 8 to 12 GHz on bibder specimens of various viscosities. An experimental matrix was developed using 3 different binders, 3 additives. The microwave permittivity was to measure the dielectric constants of the various blends at temperatures of 25, 30, 35, 40, and 45 °C. Several sets of nomo graphs were estabilished based on the observed correlation that can be used to determine the penetraion and viscosity of of saphalt binders using with the measured dielectric constant of the binder material. Such an approach is expected to be more accurate, repeatable, contactless and non-destructive to some extent. It shows a great potential to be used as a binder grading method besides the 104 conventional and SHRP methods.